Taxing ourselves : a citizen's guide to the great debate over tax reform - Slemrod, Joel (MIT Press, 2000)
Annotation A majority of Americans are dissatisfied with the current income tax system. They complain that taxes are too high, complicated, difficult, unfair, and sometimes intrusive to enforce. Yet how should the system be fixed? In Taxing Ourselves, Joel Slemrod and Jon Bakija offer a guide to the tax reform debate in clear, nontechnical language without misleading the reader with oversimplifications. The second edition takes account of tax developments through 1998, examines recent research on the economic impact of taxation, and includes a new appendix containing the key statistics on the U.S. tax system throughout its history. The book gives a historical perspective on taxation in the United States along with a concise description of our current federal income tax system. It reviews basic criteria by which tax policy should be judged and examines how the tax burden is distributed and what is known about the economic effects of taxation. The book then covers the key elements of various tax reform proposals, including a single rate, a clean base, and a consumption base. The book closes with a voter's guide to tax reform for the concerned citizen to keep handy when the rhetoric heats up - as it inevitably will during the 2000 presidential campaign - to help separate fact from fiction and reality from campaign promises.